MEDIATING JOB SATISFACTION IN REDUCING TURNOVER INTENTION OF NURSE AT RSUD dr. SOEKARDJO TASIKMALAYA - Peni Cahyati (Universitas Padjadjaran, 2021)
The aim of this study was to determine the influence of organizational culture and compensation on job satisfaction and its implications on the intention to move the nurse at the Regional General Hospital dr. Soekardjo Tasikmalaya. The results of this study can be useful practically and theoretically, i.e. as material development management of human resources, especially nurses in order to improve the quality and productivity of hospital services as well as lowering the intention of migration of nurses. The research method uses a quantitative approach, with the nature of this research was descriptive and verification. How to capture data through interviews and questionnaire with the techniques of observation and field Study, with the sampling technique of sampling is simple. The collection of Data in the field is done in 2019. Statistical analysis techniques to test hypotheses using Path Analysis. Based on the results of the analysis, it can be seen that the culture of the organization, compensation, job satisfaction and intentions to move in general is pretty good. There is the influence of organizational culture and compensation as well as job satisfaction simultaneously on work satisfaction, as well as have a negative effect on the intention to move from the nurses in the Regional General Hospital dr. Soekardjo Tasikmalaya.